Birth prevalence of encephalocele in Africa: a systematic review and meta-analysis - Mohammed Oumer; Alemnew Demissie Kassahun (BMJ Publishing Group, 2021)
Objective To identify the birth prevalence of encephalocele in Africa, 2020.Methods We carried out a systematic search of the following databases (PubMed/Medline, PubMed Central, Joanna Briggs Institute (JBI) Library, Cochrane Library, Web of Science, Google Scholar, Science Direct, African Journals Online and Embase), using search terms (prevalence, encephalocele, "neural tube defects", "cranium bifidum", "congenital malformations", "congenital defects", "structural birth defects", "structural abnormalities", newborns/neonates/ "live births"/ "stillbirths" and their MeSH Terms) up to 16 July 2021. The JBI quality appraisal checklist was used to assess the quality of studies when they were abstracted using a standardised data extraction template. The I2 statistic and Cochrane Q test were used to examine heterogeneity across studies statistically. The prevalence of encephalocele was estimated using a random-effect meta-analysis model. Subgroup, sensitivity, meta-regression and time trend analysis were carried out. The publication bias was checked using Egger and Begg's tests.Results Twenty-seven relevant studies were identified and provided a total of 5 107 109 births. In this systematic review and meta-analysis, the pooled birth prevalence of encephalocele in Africa was 0.02% (or 2 per 10 000 births) (95% CI 0.02% to 0.03%). The overall prevalence of birth encephalocele using the median from studies was 0.02% (IQR=0.01%-0.04%). Higher prevalence of encephalocele was detected in Nigeria 0.06% (95% CI 0.04% to 0.08%), Sudan 0.04% (95% CI 0.03% to 0.05%), Egypt 0.04% (95% CI 0.04% to 0.05%), DR of Congo 0.02% (95% CI 0.02% to 0.03%), Ethiopia 0.02% (95% CI −0.004% to 0.05%) and Tanzania 0.02% (95% CI 0.002% to 0.04%). The prevalence of encephalocele per live birth was 0.03% and both live birth and stillbirth was 0.03%.Conclusions This review indicates a high prevalence of encephalocele, but studies were limited suggesting the need for additional research.PROSPERO registration number CRD42021242161.